APPLICATION OF FACE-TO-FACE LEARNING IN THE NEW NORMAL ERA (Case Study: SDN 25 Pondok Hutan) - Mardia Ulfa Hasibuan; Ela Syahfriani; Rinawati Hutabarat; Mavianti Mavianti (Proceeding International Seminar of Islamic Studies, 2021)
This research entitled Application of Face-to-Face Learning in the New Normal Era (Case study: SDN 25 Pondok Hutan) aims to analyze an application of face-to-face learning in the new normal era at SDN 25 pondok Hutan. The problem that arises is that the ineffective face-to-face learning which is carried out only once a week face-to-face reduces the effectiveness of learning at school. Face-to-face learning during the pandemic in the new normal era was not very effective and made these elementary students less serious about attending face-to-face learning only once a week and wearing casual clothes. The purpose of this research is to find out how effective the application of face-to-face learning is in the new normal era today. The method used is descriptive method. It was found that the application of face-to-face learning in the new normal era during the pandemic was less effective and prevented the achievement of learning objectives. Keywords: Application of learning, effectiveness, new normal